2007
DOI: 10.1159/000112633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pitavastatin on Adiponectin in Patients with Hyperlipidemia

Abstract: The effects of treatment with pitavastatin on inflammatory and platelet activation markers and adiponectin in 117 patients with hyperlipidemia were investigated to determine whether pitavastatin may prevent the progression of atherosclerotic changes in hyperlipidemic patients. Adiponectin levels prior to pitavastatin treatment in hyperlipidemic patients with and without diabetes were lower than levels in normolipidemic controls. Both total cholesterol and the low-density lipoprotein cholesterol decreased signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 68 publications
2
36
1
Order By: Relevance
“…On the other hand, no significant reduction of the plasma MCP-1 levels was found in the pitavastatin-treated group either. We previously reported that pitavastatin could cause an elevation of adiponectin in hyperlipidemic patients with type 2 diabetes [55,56]. In these reports, we inferred two possibilities about this mechanism, which were an inhibition of production/activity of ROS and an influence on adipocyte physiology via effects on sterol regulatory element-binding proteins-1c [57].…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, no significant reduction of the plasma MCP-1 levels was found in the pitavastatin-treated group either. We previously reported that pitavastatin could cause an elevation of adiponectin in hyperlipidemic patients with type 2 diabetes [55,56]. In these reports, we inferred two possibilities about this mechanism, which were an inhibition of production/activity of ROS and an influence on adipocyte physiology via effects on sterol regulatory element-binding proteins-1c [57].…”
Section: Discussionmentioning
confidence: 88%
“…Recently, it was reported that adiponectin influences the value of HDL-C 21) . Pitavastatin increases adiponection in hyperlipidemic patients 22) . Since the concentration of adiponectin is lower in diabetes patients than non-diabetes patients 23) , adiponectin could mediate HDL-C elevation in diabeteic patients by pitavastatin.…”
Section: Discussionmentioning
confidence: 99%
“…80 Several clinical studies have also found that pitavastatin possesses an adiponectin-increasing effect in hyperlipidemic patients with and without T2D. [85][86][87][88][89][90] Adiponectin is a protein with antiatherosclerotic, anti-inflammatory, and antidiabetogenic properties exerted on liver, skeletal muscle, adipose tissue and pancreatic β-cells. 90 Mechanistically, adiponectin stimulates AMPK, a kinase that suppresses energy-consuming pathways such as hexosamine and cholesterol biosynthesis.…”
Section: Review Diabetesmentioning
confidence: 99%